1991
DOI: 10.1111/1540-6229.00566
|View full text |Cite
|
Sign up to set email alerts
|

A Price Dispersion Equilibrium in a Spatially Differentiated Housing Market with Search Costs

Abstract: An equilibrium model of search in a spatially differentiated rental housing market is formulated that predicts both rent dispersion and equilibrium vacancies. The equilibrium rent distribution is determined on the landlord's (rental supply) side given tenants' search strategies. Then tenants' optimal search strategy, denned by the share of the market a tenant searches, is determined given the costs and benefits of search and the distribution of landlords' rents. The equations of supply and demand for rental un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…2 Also note that the marginal cost of Bproduction'' is zero, and this means that the dynamic IO model, with switching production cost, may not apply to the housing market. 3 For instance, see Gabriel et al (1992), Baharad and Eden (2004), and the theoretical works of Read (1991). 4 For instance, see Greenwood and Hercowitz (1991); Kiyotaki and Moore (1997); Ortalo-Magne and Rady (1999), Chen (2001), and Law (2000) for a survey.…”
mentioning
confidence: 99%
“…2 Also note that the marginal cost of Bproduction'' is zero, and this means that the dynamic IO model, with switching production cost, may not apply to the housing market. 3 For instance, see Gabriel et al (1992), Baharad and Eden (2004), and the theoretical works of Read (1991). 4 For instance, see Greenwood and Hercowitz (1991); Kiyotaki and Moore (1997); Ortalo-Magne and Rady (1999), Chen (2001), and Law (2000) for a survey.…”
mentioning
confidence: 99%
“…At the end of the time step, the flat remains empty. This probability also depends on the rent p of the flat: π l = min(p/p l , 1), where p l is another characteristic rent, which could be related to rental provision costs in housing economics [10]. In case the rent is lowered, it is multiplied by a given factor f l < 1.…”
Section: A Simple Model Of Rental Housing Marketmentioning
confidence: 99%
“…The importance of the vacancy rate for the turnover between tenants and its influence on price formation have been underlined. Several works have studied price dispersion, and the conditions needed to model it on the housing market [9,10,11], or corresponding wage dispersion on the labor market [12,13] and general price dispersion for consumer goods [14]. The phenomenon of price dispersion is also documented in the empirical literature, be it for housing market [15,16] or prices of products in stores for instance [17].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed literature review on price dispersion can be found in Baye et al (2006). Price dispersion studies on durable and re-saleable goods such as real estate are also growing rapidly in recent years (Read 1991;Gabriel et al 1992;Baharad and Eden 2004;Leung et al 2006;andYiu et al 2006, 2007a, b). Real estate is a particularly attractive case for study because its decentralized market makes it possible to observe the dispersion of transacted prices directly.…”
Section: Previous Studiesmentioning
confidence: 99%